2004
DOI: 10.1074/jbc.m407836200
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Arginine 276 in the Leucine-loop of Human Uracil-DNA Glycosylase

Abstract: Uracil residues are eliminated from cellular DNA by uracil-DNA glycosylase, which cleaves the N-glycosylic bond between the uracil base and deoxyribose to initiate the uracil-DNA base excision repair pathway. Co-crystal structures of the core catalytic domain of human uracil-DNA glycosylase in complex with uracil-containing DNA suggested that arginine 276 in the highly conserved leucine intercalation loop may be important to enzyme interactions with DNA. To investigate further the role of Arg 276 in enzyme-DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…For human UNG the importance of residues located in this part of the loop had been shown by the drastic reduction of the catalytic efficiency for the excision of uracil bases in the context of double-stranded DNA when Arg276 is mutated 38 while activity against singlestranded DNA was less affected. A comparison of the sequences of the herpesvirus UNG leucine loops (Figure 1(b)) shows, that γ-herpesviruses share this loop structure (Figure 3(b)).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For human UNG the importance of residues located in this part of the loop had been shown by the drastic reduction of the catalytic efficiency for the excision of uracil bases in the context of double-stranded DNA when Arg276 is mutated 38 while activity against singlestranded DNA was less affected. A comparison of the sequences of the herpesvirus UNG leucine loops (Figure 1(b)) shows, that γ-herpesviruses share this loop structure (Figure 3(b)).…”
Section: Discussionmentioning
confidence: 98%
“…38 Whereas the first two functions are located on the part of the loop that is structurally conserved (sequence HPSPL in EBV), the last function is located on the more variable C-terminal side of the loop. Here the enzymes from HSV-1, D. radiodurans and Figure 1(a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for this could be that the His275 residue binds stronger to the transition state than to the ground state, affecting k cat instead of K M [39]. A strong interaction between the leucine-loop in cUNG and DNA is supported by a mutational study of Arg276 in hUNG, which shows its importance for the activity of hUNG due to favourable interactions with DNA [40].…”
Section: The H275y Substitution Severely Affects the K Catmentioning
confidence: 84%
“…These observations suggest that Arg276 may stabilize the leucine-loop and Leu272 side chain either before or after it is inserted into the DNA minor groove. Recent mutational analysis of Arg276 demonstrated that substitutions at Arg276 resulted in reduction of steady-state uracil-DNA binding, base flipping, and enzyme catalysis [12].…”
Section: Introductionmentioning
confidence: 99%